Application of low‐wavenumber Raman spectroscopy to the analysis of human teeth. (24th June 2019) - Bērziņš, Kārlis; Sutton, Joshua J.; Loch, Carolina; Beckett, Deanna; Wheeler, Benjamin J.; Drummond, Bernadette K.; Fraser‐Miller, Sara J.; Gordon, Keith C.
Abstract: Low‐wavenumber Raman spectroscopy is demonstrated for its potential to analyse mineralization abnormalities in human teeth. Four different dental samples were analysed in this study, denoted as healthy control, mild hypomineralization, enamel caries, and AI (severely degraded due to Amelogenesis imperfecta ). All specimens were imaged using principal component analysis. The spectra from low‐ wavenumber and midwavenumber regions were simultaneously collected allowing for direct comparison between the two regions. This approach provided a method to characterize structural and chemical variation within samples. Structurally different hydroxyapatite was found to be present in the surface and bulk of the enamel. The thin outer layer of the enamel contained the most structurally ordered mineral. The obtained Raman images enabled characterization and comparison of lesion domains as well as relative hydroxyapatite abundances across all dental samples. Abstract : A variety of human tooth samples were mapped using Raman spectroscopy. Data analysis was carried out using principal component analysis. This was complimented by characterization of the main hydroxyapatite Raman band ‐ ν 1 P O 4 3 − . The obtained structural information from the low‐frequency range was directly compared and correlated to spectral features in the more commonly used midfrequency region.